Thermostabilized photodiode for monitoring radiation of medical lasers - Dobrovolsky, Yu.; Pidkamin, L.; Kuzenko, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The construction of cooled photodiode for medical lasers with non-linearity of output performance in the range from 10⁻⁸ to 10⁻¹ W not more than 1.05 % is suggested. Regulation of cooling the crystal of photodiode is performed by means of specific software controlling the temperature of the photodiode crystal depending on the value of its photocurrent.